16S rRNA-based metagenomics insights into the microbial diversity and functional attributes of soils from the rhizosphere of selected C4 crops of farms in Mpumalanga and Limpopo provinces, South Africa - Mamonokane Olga Diale-Makhongela; Tiisetso Mpai; Francina Lebogang Bopape; Prudence Mtsweni; Adeola Salawu-Rotimi; Nemera Geleta Shargie; Abe Shegro Gerrano; Liesl Morey; Bongani Kubheka; Ahmed Idris Hassen (PLoS ONE, 2026)
The rhizosphere serves as a hub for a variety of microorganisms that are highly beneficial to crop production and improvement of soil health. However, intensive farming practices including utilization of agrochemicals can cause a decline in microbial diversity that could severely compromise soil health and crop productivity. Here we investigated the taxonomic abundance and functional diversity of the microbial communities of sorghum and pearl millet rhizosphere soil samples from sixteen farms in Mpumalanga and Limpopo Provinces of South Africa. Soil samples were collected at the rhizosphere of sorghum and pearl millet crops and pooled into 34 samples. The soil samples were used for 16S rRNA amplicon sequencing analysis, soil physicochemical properties, and community-level physiological profiles. The results indicated that carbon utilization was highest in the majority of soil samples from Jane Furse, which also demonstrated greater microbial richness. The 16S rRNA amplicon sequencing analysis provides insight into the relative abundance of soil microbial communities, where at phylum level Planctomycetes, Proteobacteria, and Actinobacteria were the most predominant in all farms, but their relative abundances varied. Our results revealed that physicochemical properties could affect microbial abundance and diversity. The distance-based redundancy analysis (dbRDA) explained 46.8% of the variation in the soil bacterial community structure, with Mn, Fe, NO₃⁻-N, and Ca identified as the key soil physicochemical variables shaping community composition. Thus, this study may contribute to advancing sustainable agricultural practices by providing baseline data that may inform future bioinoculant development.